نظام التوثيق وأثره في إدارة الأصول الوقفية في دولة الإمارات العربية المتحدة: نماذج من إمارة الشارقة (Documentation System and its Impact on Endowment Managements in United Arabic Emirates: The Study of Emirate of Sharjah) - مها بنت منصور الصائغ (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
شهد تاريخ الأمة الإسلامية حضارة ونهضة عالمية في جميع مجالات الحياة الإنسانية، ومما كان له كبير الأثر في ذلك هو الأوقاف التي بدأت مع سيد البشرية محمد صلى الله عليه وسلم واستمرت بتنوع وشمولية إلى عصرنا الحالي؛ ولكن ما تعرضت إليه الأوقاف من إهمال وإقصاء وضياع يرجع لأسباب عديدة من أهمها غياب التوثيق الوقفي. تقوم الدراسة على تتبع مفهوم الوقف والتوثيق، والوقف في الإمارات العربية المتحدة ول سيما في إمارة الشارقة. توصلت الدراسة إلى نتائج منها: أن الأوقاف قائمة منذ زمن بعيد، وأن رغبة الواقف بالوقف وإقدامه عليها لم ينقصها سوى وثيقة، وأنه لا وثائق لها ولا مستندات، كما أن العرض الموجز لنشأة دائرة الأوقاف بالشارقة وسعيها لإحياء سنة الوقف ونشر ثقافته نراه يتضح شيئاً فشيئاً من خلال تفعيل مواد القانون والبحث حول الأنسب والأصح لحماية الأوقاف، ولم يكن هذا الاهتمام بالوقف إلا انعكاساً لتوجه الواقفين وتماشياً لرؤية الحكام وامتثالاً لنهج خير الأنام ورغبة في تكافل الأرواح وحباً للسلام. الكلمات المفتاحيّة: الوقف، التوثيق، المقارنة، الشارقة. Abstract The history of Islamic nation has witnessed a global civilization and it has had a great impact in all areas of human life, including the endowments that began with the master of humankind; Muhammad S.A.W. and it was continuing in diversity and comprehensively until our epoch. However, there are some problems related to endowment management such as negligence, exclusion and loss that due to many reasons. Among the most important reasons is the absence of endowment documentations. Therefore, the study aims to discuss the concept of endowment and documentation, as well as the endowment in United Arabic Emirates, especially in the Emirate of Sharjah. The study concluded that the practice of endowment has been existed for a long time, yet there are in need of endowment documentations. This study also found that the information related to the establishment of institution of endowment in Sharjah and its role has spread widely to the people through the enforcement of the law and the implementation of the research related to the practice of endowment in order to sustain them in a good way. This documentation system was only a reflection of what has stated in Shariah laws regarding the practice of endowment among the donors, so that it will be in line with the approach of good intentions and love of peace. Keywords: Endowment, Documentation, Comparison, Sharjah.